Implementation of The Patas Model in The Development of The Matana University Graduation Information System - Barus, Simon Pranata (JISA(Jurnal Informatika dan Sains), 2022)
There is an urgent need to make a graduation information system at Matana university. This system is needed, especially for students, secretariat, and finance. Several other things to consider, namely the number of participants and the graduation committee are more than 300 people, delegation of system development to one person, many users are still unfamiliar with integrated information systems based on information technology (IS/IT), the Corona pandemic, and can anticipate sudden changes. Therefore, we need a software development model that fits these conditions. The research methods for making this model, such as literature study, interviews, observation, model making and model testing (model application). This software development model is called Patas, it is fast and limited. This model has six stages, i.e., user needs, tools selection, modification, evaluation, implementation, and maintenance. This model is then applied to the development of a graduation information system at Matana University. The Matana University graduation information system has been successfully built using the Patas model. This system features prospective graduate registration, payment, sending information to participants (personal or mass) by email, dashboard, privilages user, attendance for graduates by barcode, change profile and content management. This graduation information system is used from graduation preparation to graduation day. Thus, the Patas model can be an alternative model in software development. In the future, the Patas model needs to be tested for the development of a different and larger system.